(untitled) (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The presence of lactic acid bacteria (LAB) in the vaginal microbiota is fundamental for reproductive health, primarily due to their role in sustaining an acidic pH and providing a defense against urogenital pathogens. The aim of this study was to identify six bacterial isolates (G 4.4 G 13.1, G 21.K.2, G38.0.1, G42.10.2 and G46.M.3) from the vaginal microbiome that had previously demonstrated strong antagonistic activity. The identification of the studied isolates was performed using classical bacteriological methods based on the analysis of their morphological, physiological, and biochemical characteristics. MALDI-TOF MS analysis was conducted in duplicate using the Bruker Microflex® LT/SH smart system (Bruker Daltonics, Bremen, Germany). All tested strains showed limited growth on the surface of MRS agar and produced lenticular or round, milky-white colonies measuring up to 1 mm in diameter within the depth of the agar. Research indicates that the optimal temperature for growth of the studied strains is generally 37℃, whereas strains G 13.1 and G46.M.3 exhibit optimal growth at 33℃. None of the isolates synthesized indole or deaminated arginine. All were negative for oxidase, catalase, urease, and amylase activities, exhibited homofermentative metabolism, and tested positive for gelatinase. The G46.M.3 isolate exhibits lipolytic and caseinolytic activities. The isolates demonstrated the ability to ferment a wide range of carbohydrates. According to MALDI-TOF MS analysis, strain G 4.4 was identified as Lactobacillus delbrueckii subsp. lactis, G 13.1 as Lacticaseibacillus rhamnosus, G 21.K.2 as Lactobacillus delbrueckii subsp. lactis DSM 20355, G 38.0.1 as Lacticaseibacillus paracasei, G 42.10.2 as Lacticaseibacillus rhamnosus, and G 46.M.3 as Enterococcus faecalis 20247_4 CHB. These results enhance the understanding of vaginal microbiota composition and highlight specific LAB with potential probiotic properties. Their demonstrated antagonistic activity suggests a promising role in supporting vaginal and reproductive health.